A Heart Rate Based Algorithm to Estimate Core Temperature Responses in Elite Athletes Exercising in the Heat - de Korte, Johannus Q.; Veenstra, Bertil J.; van Rijswick, Mark; Derksen, Eline J. K.; Hopman, Maria T. E.; Bongers, Coen C. W. G.; Eijsvogels, Thijs M. H. (Frontiers in Sports and Active Living, 2022)
Purpose: Non-invasive non-obtrusive continuous and real-time monitoring of core temperature (Tc) may enhance pacing strategies, the efficacy of heat mitigation measures, and early identification of athletes at risk for heat-related disorders. The Estimated Core Temperature (ECTempTM) algorithm uses sequential heart rate (HR) values to predict Tc. We examined the validity of ECTempTM among elite athletes exercising in the heat. Methods: 101 elite athletes performed an exercise test in simulated hot and humid environmental conditions (ambient temperature: 31.6±1.0°C, relative humidity: 74±5%). Tc was continuously measured using a validated ingestible telemetric temperature capsule system. In addition, HR was continuously measured and used to compute the estimated core temperature (Tc-est) using the ECTempTM algorithm. Results: Athletes exercised for 44±10 min and n=5,025 readouts of Tc (range: 35.8°C to 40.4°C), HR (range: 45 bpm - 207 bpm), and Tc-est (range: 36.7°C to 39.9°C) were collected. Tc-est demonstrated a small yet significant bias of 0.15±0.29°C (p<0.001) compared to Tc, with a limit of agreement of ±0.45°C and a root mean square error of 0.35±0.18°C. Utilizing the ECTempTM algorithm as a diagnostic test resulted in a fair to excellent sensitivity (73% to 96%) and specificity (72% to 93%) for Tc-est thresholds between 37.75°C and 38.75°C, but a low to very-low sensitivity (50% to 0%) for Tc-est thresholds >39.0°C, due to a high prevalence of false-negative observations. Conclusion: ECTempTM provides a valuable and representative indication of thermal strain in the low- to mid-range of Tc values observed during exercise in the heat. It may, therefore, be a useful non-invasive and non-obtrusive tool to inform athletes and coaches about the estimated core temperature during controlled hyperthermia heat acclimation protocols. However, the ECTempTM algorithm, in its current form, should not solely be used to identify athletes at risk for heat-related disorders due to low sensitivity and high false-negative rate in the upper end of the Tc spectrum.